MANAGEMENT CONTROL SYSTEM OF STATE TRANSPORT UNDERTAKING- AN ANALYSIS OF HARYANA ROADWAYS - Jain, Seema (Archives of Business Research, 2018)
Since centuries for overall development of nation and human civilization transport had played a vital role and changed the way of life of the human being. Public transport is to provide people with mobility and access to employment, education, retail, health and recreational facilities, as well as community facilities. The primary objective of Public transport is to provide public service. The infrastructural development and inter connecting villages with cities, lifting the goods and providing services to the people to visit one place to another transport have proved a boom in the economy. The more trips that are made by public transport reduces the number of trips that are made by private vehicles, leading to less congestion on the roads and a more efficient road system. The present paper studies Haryana State Road transport Undertaking as an organization from the aspect of control system and their effectiveness. For the goal consonance of this study Simon’s four levers of control model applied.